MANAJEMEN PEMBELAJARAN BERBASIS 7 KEBIASAAN ANAK INDONESIA HEBAT UNTUK PEMBENTUKAN KEMAMPUAN SPIRITUAL ANAK DI TK IT IQRA SERANG - Devi, Meisya Aulia; Cucu Atikah; Fadlullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of learning management based on the 7 Habits of Great Indonesian Children in developing the spiritual abilities of early childhood students at TKIT Iqra Serang. This research employed a qualitative approach with a descriptive method. The research subjects consisted of the principal and classroom teachers. Data were collected through observation, interviews, and documentation. The results showed that learning management was carried out through planning, organizing, implementation, and evaluation stages integrated into daily learning activities. Teachers acted as facilitators, role models, and motivators in instilling positive habits in children. The implementation of the 7 Habits of Great Indonesian Children had a positive impact on children’s spiritual development, including worship awareness, discipline, responsibility, and positive social behavior. Therefore, the implementation of habit-based learning management can effectively support character building and spiritual development in early childhood education Kata kunci : learning management, 7 habits of great Indonesian children, spiritual ability, early childhood, character education